The Dirichlet problem for m-subharmonic functions on compact sets - Åhag, Per; Czyż, Rafał; Hed, Lisa (MATHEMATICA SCANDINAVICA, 2020)
We characterize those compact sets for which the Dirichlet problem has a solution within the class of continuous m-subharmonic functions defined on a compact set, and then within the class of m-harmonic functions.